A CHANGE IN THE WAY ARTILLERY IS USED, BASED ON THE RUSSIA-UKRAINE CONFLICT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Artillery for the execution of firing tasks is deployed in a battle order, which from а long years ago was aimed at massed fire and hitting targets with the use of a large amount of ammunition from the force for artillery support. Different configurations were applied to the means of defeat, depending on the probable threats and countermeasures against the artillery during the period of time that can be specified as expired. This tactic is also used in the initial phase by both sides of the conflict between Russia and Ukraine sinse  2022. The introduction of new means of countermeasures against artillery systems and the improvement of existing ones imposes changes on the battlefield, concerning the determination of data for firing per hit and the number of guns used. One of the important elements affecting this is the time, both for preparation and for staying at firing positions on the guns. No less important is the amount of artillery systems used, which practice shows that reduced to one or two units from batteries and divisions used in the past, gives the desired effect, combined with improved accuracy of fire and increased survivability on the battlefield for artillery. The combination of all this with a timely and covert maneuver provides direction for the development of artillery tactics in recent years , which reflects both the requirements for artillery systems and the ability to Fire for Effect.